Structure of Bird Communities of Four Green Areas of the City of Asunción, Paraguay - Martin-Etchegaray, Alan (2018)
Many studies have shown a negative impact of urbanization on biodiversity, producing a homogenization of the communities, even extirpating native species and expanding species more adapted to urbanization, including some exotic ones. Asunción has high rates of urban growth, so it is important to know the status of bird communities that house their green areas. The present study has evaluated the richness, diversity, and structure of the bird community that occurs in urban green areas of the city. We have sampled the avifauna of four green areas (5.8-282 hectares) to compare the structure of these communities and to test the hypothesis of island size in the urban environment. We located four counting stations in areas of groves and forest edges in each area. Each station was visited six times during the study, with 10-minute counting points, with a radius of 30 m, in which the birds heard or observed were recorded. A total of 95 species were recorded in the green areas during the study, including two introduced species (Columba livia and Passer domesticus). The species accumulation curves showed that the sampling efforts were appropriate for the areas, except for the larger one. The larger areas had greater species richness (range = 30-61 species), higher diversity index (range = 2.62-3.48), and a greater number of species with low relative abundance. The smaller fragments presented greater dominance of generalist species. The richness and diversity had a significant positive correlation with the size of the areas. The abundance obtained a negative correlation with the area of the park, although not significant. The results show that the maintenance of large urban green areas will allow a greater wealth of birds, with a diversity of species with relatively low abundance, and with a low dominance of generalist species.